Identification of Genes in Positive Alleles Marking Type 2 Diabetes Mellitus Using Primer A18: Identifikasi Gen pada Alel Positif Penanda Diabetes Melitus Tipe 2 Menggunakan Primer A18 - Firda, Aminatul; Mushlih, Miftahul (Universitas Muhammadiyah Sidoarjo, 2021)
Diabetes mellitus type 2 (DMT2) is a disorder characterized by hyperglycemia due to impaired insulin secretion and insulin resistance. The purpose of this study was to identify the gene involved in the positive allele of DMT2 marker using A18 primer and is a type of exploratory descriptive study. The samples used were 2 samples of DMT2 patients from the villages of Taman and Balongbend, and 8 samples of DNA collection at the Molecular Biology Laboratory, Muhammadiyah University of Sidoarj. Based on the genetic analysis carried out, the GATB gene (Glutamyl-tRNA Amidotransferase Sub Unit B) was identified in the positive allele with a homology value of